Healing Study of Porcine Heart Transapical Wounds Closed Using a Remote Automated Suturing Technology. Issue 1 (January 2013) - Wilshire, Candice L.; Kaufer, James W.; Gorea, Heather R.; Sauer, Jude S.; Knight, Peter A.
Objective: A safe and reliable direct percutaneous approach for transapical access to the left ventricle would be a significant advance toward decreasing the invasiveness of intracardiac interventions. This report presents results from a surviving porcine beating heart model in which transapical access sites were closed using an automated suturing technique ultimately intended for percutaneous use. Methods: Through an approved protocol including general anesthesia, the cardiac apex in 10 beating pig hearts was surgically exposed, permitting transapical passage of a 0.035-in guidewire and a 5.5F, 0.9-mL Fogarty balloon catheter. An automated suturing device was passed over the guidewire and the Fogarty onto the transapical access site. Two pledgeted horizontal mattress sutures were simultaneously placed concentrically around the apical access site with a single squeeze of the device's lever. A 25F dilator was passed into the left ventricle over the guidewire and subsequently removed. The sutures were then secured using pledgeted titanium knots. Chest wall and skin incisions were closed. The animals were recovered from anesthesia and resumed a normal diet. Results: Under general anesthesia, the transapical access site of each animal was re-exposed, five at 1-week and five at 2-week intervals. Hemostasis was complete, and all wounds healed well. Conclusions: The evaluation of transapical wound closures in this surviving porcine heart model demonstrates complete hemostasis and excellent healing through the use of this automated remote suturing technology.